EXPLORING OBSTACLE COURSE GAMES IN PHYSICAL EDUCATION TO IMPROVE GROSS MOTOR SKILLS AND SELF-CONFIDENCE - Bunyamin Bunyamin; Erwin Setyo Kriswanto (Jurnal Kajian Pendidikan dan Psikologi, 2026)
This study aimed to explore the implementation of Obstacle Course games in Physical Education, Sports, and Health (PJOK) instruction and to identify their contributions to the development of elementary school students’ gross motor skills and self-confidence. The study employed a qualitative approach with a case study design conducted among fourth-grade students at SD Negeri 002 Rantau Pulung. The research informants consisted of a PJOK teacher, students purposively selected based on variations in motor skills and self-confidence, and peers as supporting informants. Data were collected through participant observation, semi-structured interviews, documentation, and field notes. Data trustworthiness was strengthened through source, technique, and time triangulation, member checking, peer debriefing, and an audit trail. Data were analyzed using an interactive model consisting of data condensation, data display, and conclusion drawing and verification. The findings indicate that the implementation of the Obstacle Course provided students with active, progressive, and adaptive learning experiences. Improvements in gross motor skills were reflected in enhanced coordination, balance, agility, directional changes, body control, and independence in completing obstacle sequences. Meanwhile, self-confidence developed through increased willingness to try, persistence in facing failure, active participation, and readiness to complete challenges independently. Scaffolding, demonstrations, teacher feedback, difficulty-level modifications, and peer support emerged as important mechanisms facilitating these changes. This study confirms that Obstacle Course activities can serve as a pedagogical strategy that integrates the development of motor competencies and psychosocial skills in elementary school PJOK instruction.